1985
DOI: 10.1007/bf00379383
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid peroxide level and blood superoxide dismutase activity in workers with occupational exposure to lead

Abstract: We studied whether lead exposure increased the serum lipid peroxide (LPO) level and inhibited blood superoxide dismutase (SOD) activity in workers with occupational exposure to lead and rats injected with lead. We examined the following subjects: (1) manual workers (712 males) from 18 to 59-years-old in steel production with occupational exposure to lead, (2) office workers (155 males) without exposure to lead, (3) rats subcutaneously injected with lead in concentrations of 10 or 20 mg/kg as lead acetate. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
30
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 15 publications
9
30
2
Order By: Relevance
“…Our previous studies (Ercal et al 1996;Gurer et al 1998Gurer et al , 1999a as well as the present one support the hypothesis indicated by several other groups (Ribarov and Bochev 1982;Ito et al 1985;Monterio et al 1985Monterio et al , 1991Lawton and Donaldson 1991;Sandhir et al 1994;Solliway et al 1996) that Fig. 2.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies (Ercal et al 1996;Gurer et al 1998Gurer et al , 1999a as well as the present one support the hypothesis indicated by several other groups (Ribarov and Bochev 1982;Ito et al 1985;Monterio et al 1985Monterio et al , 1991Lawton and Donaldson 1991;Sandhir et al 1994;Solliway et al 1996) that Fig. 2.…”
Section: Discussionsupporting
confidence: 92%
“…Various reports regarding influence of lead on SOD and CAT activities have given divergent results. Some studies showed decreased activities of SOD and CAT (44,45), and others showed increased activities (46,47). In our study we observed a significant decrease in CAT and SOD activities in painters compared to controls (Table 1).…”
Section: Figure 1 Correlation and Regression Between Blood Lead Levelsupporting
confidence: 62%
“…Four studies reported that TBARS were detected measuring LPO in body fl uids. Three studies reported that the TBARS concentration was signifi cantly higher in workers exposed to lead than in control groups (Ito et al 1985 ;Sugawara et al 1991 ;Wasowicz et al 2001 ), and another study showed no signifi cant differences among subjects with higher BLLs (Malekirad et al 2010 ). A higher correlation of serum LPO was observed with the duration of lead exposure than with aging (Ito et al 1985 ).…”
Section: Lead-induced Oxidative Stress In Occupationally Exposed Popumentioning
confidence: 92%
“…Three studies reported that the TBARS concentration was signifi cantly higher in workers exposed to lead than in control groups (Ito et al 1985 ;Sugawara et al 1991 ;Wasowicz et al 2001 ), and another study showed no signifi cant differences among subjects with higher BLLs (Malekirad et al 2010 ). A higher correlation of serum LPO was observed with the duration of lead exposure than with aging (Ito et al 1985 ). One study measured the production of isoprostane to check the oxidation of tissue phospholipids and observed increased isoprostane levels in welders when compared with the control group; it also identifi ed that age and cigarette smoking did not contribute to the 2.4-fold increase in the isoprostane levels observed in welders (Han et al 2005 ).…”
Section: Lead-induced Oxidative Stress In Occupationally Exposed Popumentioning
confidence: 98%